THE ESTIMATION METHOD OF RESIDUAL RESOURCE OF PLATTER PORCELAIN INSULATORS - Kim, Ye. D.; Sychenko, V. H.; Taran, V. M. (Science and Transport Progress, 2008)
The efficiency of sorting of defective dish-shaped porcelain insulators on the criterion of tgδ ≥ 0,08 is justified. It is demonstrated the possibility of estimation of the insulation condition and remaining resource of the insulators on a railway line under operation by means of selective measurement of tgδ.